Digitization of Archival Collections by Libraries in Pakistan: Issues, Strategies, Challenges and Opportunities - Bushra A. Jaswal (Pakistan Journal of Information Management & Libraries, 2016)
In the backdrop of a case of a major archive digitization initiative completed by a Library in Pakistan to preserve a decaying last copy of an Urdu News Magazine from 18th century, the author highlights the threats to documentary heritage in general and in Pakistan in particular. The paper gives a comprehensive discussion of the digitization process, its issues, challenges and constraints by highlighting how in Pakistan, libraries and documentary heritage are facing neglect and a threat for extinction due the environmental, economic and political conditions and human threats like terrorism. Discussing the practical and operational problems of digitization work in an environment where the archival digitization is not a common practice, the paper suggests some workable strategies and solutions to overcome the barriers and bottlenecks. The paper is a good example to educate the future digitizers in Pakistan and offers workable suggestions and many thought provoking ideas for local librarians for saving the decaying archives and rare materials held in their libraries, by collective and collaborative digitization efforts.